Design and Development of Thoracic Lumbar Sacral Orthosis Brace to Reduce Back Pain - Agus Santosa; Andre Irwanto; Husnul Khotimah (Universitas Muhammadiyah Yogyakarta, 2022)
Background: Doing activities that burden the back, such as bending over for a long time and lifting weights in the wrong position, can cause injury to the spine, leaving back pain. Thoracic Lumbar Sacral Orthosis Brace (TLSO Brace) is a tool used to support the spine so that it can prevent such an injury. Objective:This research aims to design and pilot a new ergonomic TLSO Brace that can be used to improve posture, reduce back pain and prevent back pain.Methods: This research is divided into several stages, namely designing, manufacturing, and testing.Results: The results show that the level of ergonomics is mainly in the Good category. The use of the TLSO Brace was proven effective in reducing back pain intensity (p0.0001); the average pain was reduced after 14 minutes. The results also found that all respondents who used the brace at work felt no back pain. It can be seen that the lordosis back arch becomes upright after using it, meaning the tool also improves posture.Conclusions: The ergonomic TLSO Brace has been created and can improve body posture, reduce pain intensity and prevent back pain from recurring.